Social inequalities in childhood asthma - Angela Pinot de Moira, PhD; Adnan Custovic, MD, PhD, FMedSci (World Allergy Organization Journal)
Asthma is a complex, heterogeneous condition, broadly characterized by chronic airway inflammation with variable expiratory airflow limitation, but with several subtypes underpinned by different (although likely overlapping) pathological mechanisms. It is one of the most common chronic diseases of childhood and represents a significant cost for healthcare systems and affected families. Evidence suggests that a disproportionate proportion of this burden falls on families from disadvantaged socioeconomic circumstances (SECs).In this review, we describe the extent to which growing up in disadvantaged SECs is associated with an increased risk of childhood asthma diagnosis and asthma outcomes, including how this differs geographically and across different asthma subtypes. We also discuss the complex and interdependent mediating pathways that may link disadvantaged SECs with childhood asthma and asthma-related outcomes.In high-income countries (HICs), there is a fairly consistent association between growing up in disadvantaged SECs and increased prevalence of childhood asthma. However, evidence suggests that this social patterning differs across different asthma subtypes, with asthma phenotypes associated with disadvantaged SECs being less likely to be associated with atopy and more likely to begin in infancy and persist into adolescence. Disadvantaged SECs are also associated with worse asthma outcomes, which may contribute to the persistence of symptoms among disadvantaged children.In low- and middle-income countries (LMICs), the patterns are more variable and data more limited, but there is some evidence that disadvantaged SECs and atopic asthma are similarly negatively associated. There are also clear disparities in asthma outcomes, with LMICs having disproportionately high asthma-related morbidity and mortality, despite having lower asthma prevalence. A lack of accessibility to essential medication and appropriate care no doubt contributes to these disparities.The pathways leading to social inequalities in asthma are complex and interdependent, and as yet not fully understood. There is a clear need for further research into the relative importance of potential mediating pathways, including how these vary across the life course and across asthma subtypes. A stronger understanding of these pathways will help identify the most effective policy entry points for intervention, ultimately reducing inequalities across the life course.